2021
DOI: 10.3390/sym13030418
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Time-Fractional Equivalent Width Equations That Describe Hydromagnetic Waves

Abstract: The present research article is related to the analytical investigation of some fractional-order equal-width equations. The homotopy perturbation technique along with Elzaki transformation is implemented to discuss the fractional view analysis of equal-width equations. For better understanding of the proposed procedure some examples related to equal-width equations are presented. The identical behavior of the derived and actual solutions is observed. The proposed technique can be modified to study the fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Fractional calculus is one of the interesting generalizations of classical calculus, as most of the differential equations are fractional in modeling real world problems [1][2][3]. So the fractional integral inequalities are the interesting area of research for many researchers of analysis and inequality [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractional calculus is one of the interesting generalizations of classical calculus, as most of the differential equations are fractional in modeling real world problems [1][2][3]. So the fractional integral inequalities are the interesting area of research for many researchers of analysis and inequality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Discrepancies in scope (2) Discrepancies in the description of the research reported (3) Discrepancies between the availability of data and the research described (4) Inappropriate citations…”
mentioning
confidence: 99%
“…In Figure 6, we have visualized the behavior of the exact and approximate solutions for the Problem 3 using N � 20 2 , β 1 � β 2 � β 3 � 0.5, and t � 0.1, which show that the approximate solution is very compatible with the exact solution. In Figure 7, the absolute error is displayed for Problem 3.…”
Section: Complexitymentioning
confidence: 95%
“…Partial derivatives provide a flexible model and an extraordinary tool for description of capturing the history of the variable and genetic characteristics of various dynamic systems. Extensive research has been carried out in the advancement of numerical and analytical solutions of linear and nonlinear FPDEs [1][2][3][4][5][6]. However, several researchers have not succeeded in deriving and modeling many complex phenomena utilizing linear or nonlinear PDEs with integer order [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several more authors and scientists believe that this technique can be utilized to evaluate, respectively, fractional and integer fuzzy differential equations. Due to the multiple applications of the fuzzy differential equation to simulate unknown processes in a range of fields, including business, physical sciences, and biology, see references [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%